1993
DOI: 10.1029/93ja01920
|View full text |Cite
|
Sign up to set email alerts
|

In situ diagnostics of ionospheric plasma with the resonance cone technique

Abstract: Electron density and temperature profiles in the mid latitude ionosphere are derived from the ”resonance cone” in the radiation pattern of high‐frequency point antennas aboard a sounding rocket. By comparing the shapes for reversed wave propagation direction it is possible to study electron drift motion and field‐aligned beams. The data from the COREX‐I (Cooperative Resonance Cone Experiment) experiment show close agreement of electron density and temperature profiles from resonance cones with results from ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…We now strongly believe that some heat source is still missing (Oyama and Hirao, 1980), that can elevate electron temperature higher than neutral temperature (Oyama, 2000;Rohde et al, 1993), or that the current theory on T e uses incorrect parameter values, such as suggested by Jain et al (1981) on the electron temperature in the equatorial electrojet. Further neutral density, which we usually take from MSIS, might differ from the real one (Kurihara and Oyama, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We now strongly believe that some heat source is still missing (Oyama and Hirao, 1980), that can elevate electron temperature higher than neutral temperature (Oyama, 2000;Rohde et al, 1993), or that the current theory on T e uses incorrect parameter values, such as suggested by Jain et al (1981) on the electron temperature in the equatorial electrojet. Further neutral density, which we usually take from MSIS, might differ from the real one (Kurihara and Oyama, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As the turbulent shadow is formed in opposition to the wind direction, ions have difficulty to be collected by the rocket surface, which faces in the opposite direction to the wind, due to the larger collision frequency between the ions and neutrals. Electrons can directly hit the rocket body along the magnetic field, because at the place where the electric field is radial to the rocket axis, electron does not experience an E×B drift around the rocket (Rohde et al, 1993). As ions are collected only by the surface area which faces the neutral wind, the rocket will become more negative in the strong neutral wind region.…”
Section: Fig 4 Height Profile Of the Ion Current From The V-i Charamentioning
confidence: 99%
“…A source of uncertainty for the DC electric ®eld measurements is the variation in the local ®eld introduced by the rocket itself. These have been discussed by for instance Rohde et al (1993), but seem to be of importance only at the sheaths in vicinity of the body, not at the position of the boom-mounted probes.…”
Section: Electric Field Measurementmentioning
confidence: 99%
“…Almost without exception the surface of the electrode is contaminated. However even we remove the effect of electrode contamination or use the instrument which can avoid the electrode contamination (Hirao and Oyama, 1970;Oyama and Hirao, 1976), T e measured by DC Langmuir probe is higher than model T n (Oyama et al, 1980;Duhau and Azpiazu, 1985;Amemiya et al, 1985), although very rarely we observed T e which is very close to T n (Hirao and Oyama, 1973;Rohde et al, 1993).…”
Section: Introductionmentioning
confidence: 72%